Hubungan Usia, Tingkat Pendidikan Ibu, dan Pengetahuan Ibu dengan Balita Wasting - Akbar, Aysha Ayunda; Dinar Putri Rahmawati (Pusat Riset dan Inovasi Nasional, 2026)
Wasting in toddlers remains a major public health problem in Indonesia and reflects a condition of acute malnutrition that occurs over a relatively short period. Wasting can negatively affect child growth and development, weaken the immune system, cause delays in cognitive and motor development, and increase the risk of morbidity and mortality in children. Various maternal factors are believed to influence the nutritional status of toddlers, including maternal age, education level, and knowledge related to nutrition and childcare. This study aimed to determine the relationship between maternal age, maternal education level, and maternal knowledge with the incidence of wasting among toddlers in the working area of the Gempol Community Health Center, Cirebon Regency. This study employed an observational analytic design with a cross-sectional approach. The study population consisted of mothers with toddlers, and data were collected through interviews and anthropometric measurements. Data analysis was conducted using Spearman and Pearson correlation tests. The results showed that maternal education level was significantly associated with wasting in toddlers (p = 0.03). Meanwhile, maternal age (p = 0.12) and maternal knowledge (p = 0.90) were not significantly associated with wasting. These findings indicate that maternal education plays an important role in preventing wasting in toddlers. Therefore, strengthening maternal education and nutrition-related information is essential to reduce the prevalence of wasting.